Educational supervision and school culture in Spain. Genesis, constituent process and update of functions - José María HERNÁNDEZ DÍAZ (Ediciones Universidad de Salamanca, 2019)
This paper offers a historical and genetic answer of the educational supervision in Spain, from its origins in the 19th century to the present. The school supervision, necessary function and essential organism of a contemporary educational system, can only be explained from the socioeducational context it serves, from the great laws of education that define the educational policy of a country, to its concretion in the school culture of a educational establishment. At the same time, this paper think over historically on the construction of the profession of supervisor, from its training, the associative articulation, the link to the scientific production in pedagogy or sciences of education, publications and magazines of their associations or the body of supervisors. Finally, some of the challenges facing school inspection at the beginning of the 21st century are presented.